Territorial Dynamics and Urban Inequalities: A Comparative Analysis of Mato Grosso Cities Based on the Municipal Sustainable Development Index – IDSC - Oliveira, Caio Cesar Tomaz de; Nunes, Nivalda da Costa; Silva, Leticia Barros (Technical and Scientific Journal Green Cities, 2025)
Objective - The main objective of this study is to analyze and describe the level of engagement and progress of ten municipalities in the state of Mato Grosso in relation to the United Nations (UN) Sustainable Development Goals (SDGs). Methodology - The present study adopts a quantitative and descriptive approach, based on the analysis of secondary data presented in bar charts. The method employed is comparative performance analysis, where the scores attributed to each municipality in relation to the specific SDGs of each axis (Environmental: SDGs 6, 7, 12, 13, 14, 15; Economic: SDGs 8, 9, 10, 11; Institutional: SDGs 16, 17) are compared among the cities and across different objectives. The interpretation of the data aims to identify patterns, anomalies, and trends in the municipalities’ fulfillment of SDG requirements. Originality/Relevance - The study addresses a theoretical gap in the evaluation of municipal performance regarding the SDGs, especially in specific regional contexts such as Mato Grosso, a state of great environmental and economic relevance to Brazil. The literature on the localization and implementation of the 2030 Agenda at the subnational level still lacks detailed analyses that allow for the identification of nuances in progress and obstacles in different municipal realities. Results - The municipalities of Mato Grosso show heterogeneous performance across the SDGs. In the Environmental axis, they excel in Water and Sanitation (SDG 6) and Clean Energy (SDG 7), but face challenges in Life Below Water (SDG 14) and Life on Land (SDG 15). In the Economic axis, there is progress in Sustainable Cities (SDG 11) and Reduced Inequalities (SDG 10), yet performance is consistently low in Industry and Innovation (SDG 9). In the Institutional axis, cities demonstrate advancements in Effective Institutions (SDG 16), but show widespread weakness in Partnerships and Means of Implementation (SDG 17). Theoretical/Methodological Contributions - Methodologically, the research demonstrates the applicability of comparative performance analysis of multiple SDGs for a comprehensive diagnosis of sustainability at the municipal level, providing a descriptive model that can be replicated in other regions to identify potentials and priority intervention areas. Social and Environmental Contributions - By identifying the SDGs in which municipalities demonstrate fragility, the study allows for directing investments and actions towards critical areas, such as the conservation of fluvial and terrestrial ecosystems, the promotion of innovation and sustainable infrastructure, and the strengthening of partnerships for resource mobilization.